Pilot Trial on Ischemic Conditioning of the Gastric Conduit in Esophageal Cancer: Feasibility and Impact on Anastomotic Leakage (TIGOAL-I) - María-Carmen Fernández-Moreno, MD, PhD; María Eugenia Barrios Carvajal, MD; Fernando López Mozos, MD, PhD; Roberto Martí Obiol, MD, PhD; Jorge Guijarro Rozalén, MD, PhD; Elisabetta Casula, MD, PhD; Joaquín Ortega, MD, PhD (Annals of Surgery Open)
Objective:. To evaluate the feasibility, safety, and effectiveness of gastric conditioning using preoperative arterial embolization (PAE) before McKeown esophagectomy at a tertiary university hospital. Background:. Cervical anastomotic leakage (AL) is a common complication of esophagectomy. Limited clinical evidence suggests that gastric conditioning mitigates this risk. Methods:. This pilot randomized clinical trial was conducted between April 2016 and October 2021 at a single-center tertiary hospital. Eligible patients with resectable malignant esophageal tumors, suitable for cervical esophagogastrostomy, were randomized into 2 groups: one receiving PAE and the other standard treatment. The primary endpoints were PAE-related complications and incidence of cervical AL. Results:. The study enrolled 40 eligible patients. PAE-related morbidity was 10%, with no Clavien-Dindo grade III complications. Cervical AL rates were similar between the groups (35% vs 25%, P = 0.49), even when conduit necrosis was included (35% vs 35%, P = 1). However, AL severity, including conduit necrosis, was higher in the control group according to the Clavien-Dindo ≥IIIb (5% vs 30%, P = 0.029) and Comprehensive Complication Index (20.9 vs 33.7, P = 0.01). No significant differences were found in other postoperative complications, such as pneumonia or postoperative mortality. Conclusions:. PAE is a feasible and safe method for gastric conditioning before McKeown minimally invasive esophagectomy and shows promise for preventing severe AL. However, further studies are required to confirm its efficacy.